Negative pole piece, lithium ion battery and electronic device
By adopting a double-layer coating structure in the negative electrode sheet of the lithium-ion battery and using hard carbon and graphite silicon carbon materials, the problems of low energy density and poor circulation performance of the lithium-ion battery are solved, and better comprehensive performance and stability are achieved.
Patent Information
- Application Number
- CN202411996436.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The energy density of existing lithium-ion batteries is low, and the volume expansion of silicon-based materials during the charge and discharge cycle is severe, resulting in poor conductivity and reduced circulation performance.
The negative electrode sheet with a double-layer coating structure is adopted. The first coating layer contains hard carbon and the second coating layer contains graphite and silicon carbon materials. The expansion and circulation performance are improved by adjusting the composition and proportion of the two coating layers.
It improves the circulation performance, expansion performance and energy density of lithium-ion batteries, extends the battery life and improves stability.
Smart Images

Figure CN119812209A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium batteries, and in particular relates to a negative electrode plate, a lithium-ion battery and an electronic device. Background Art
[0002] Lithium-ion batteries have the characteristics of high energy density, high operating voltage, and light weight, so they are widely used in electronic products such as mobile phones, laptops, and cameras. As the performance requirements for electronic products increase, the performance requirements for lithium-ion batteries are also gradually increasing. For example, due to the continuous demand for battery life, the demand for volume energy density of batteries in the consumer electronics field continues to increase, and the gram capacity of the existing graphite negative electrode materials has also been developed to a ceiling. Improving energy density requires the introduction of new high-gram capacity negative electrode active materials.
[0003] Silicon-based materials have a theoretical capacity of up to 3600mAh / g and a charge-discharge voltage platform similar to that of graphite. They have broad prospects for application in lithium-ion batteries and are the best solution to the problem of low energy density of lithium-ion batteries. However, during the charge-discharge cycle, as lithium ions are embedded and extracted, silicon-based materials undergo huge volume changes, causing the silicon-based materials to pulverize and separate from the current collector, resulting in poor conductivity of the negative electrode and reduced cycle performance of lithium-ion batteries.
[0004] Therefore, it is crucial to introduce low-expansion negative electrode active materials to reduce the volume expansion of the negative electrode sheet during the charge and discharge cycle. Summary of the invention
[0005] In view of the above-mentioned problems in the prior art, the first aspect of the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode coating layer arranged on the surface of the negative electrode collector, and the negative electrode coating layer includes a first coating layer and a second coating layer, the first coating layer is located on the surface of the negative electrode collector, and the second coating layer is located on the surface of the first coating layer; the first coating layer contains hard carbon, and the second coating layer contains graphite and silicon-carbon material; the thickness of the first coating layer accounts for 20% to 85% of the thickness of the negative electrode coating layer.
[0006] In the negative electrode plate provided in the present application, the first coating layer contains hard carbon, and the addition of hard carbon can effectively improve the expansion and cycle performance of the negative electrode plate; the second coating layer contains graphite and silicon-carbon material, and the addition of silicon-carbon material can effectively increase the capacity of the negative electrode plate, and when mixed with graphite, the expansion of silicon-carbon material can be alleviated.
[0007] In some embodiments of the present application, the thickness of the first coating layer accounts for 25% to 75% of the thickness of the negative electrode coating layer, which can comprehensively improve the expansion of the negative electrode plate and enhance the cycle performance and energy density of the lithium-ion battery, so that the lithium-ion battery has better overall performance.
[0008] In some embodiments of the present application, the thickness of the first coating layer accounts for 45% to 65% of the thickness of the negative electrode coating layer, which can further improve the overall performance of the lithium-ion battery.
[0009] In some embodiments of the present application, gaps exist inside the graphite particles, which can further improve the expansion of the negative electrode sheet.
[0010] In some embodiments of the present application, within the range of 50 μm×50 μm on the cross-section of the negative electrode coating layer along the thickness direction, the ratio of the number of graphite particles to the number of silicon-carbon material particles is 0.20-2.00, preferably, the ratio of the number of graphite particles to the number of silicon-carbon material particles is 0.50-1.80, which can further alleviate the expansion of the negative electrode sheet, improve the cycle performance of the lithium-ion battery, and take into account the high energy density of the lithium-ion battery.
[0011] In some embodiments of the present application, a spot scanning test is performed on the silicon content in the second coating layer within a range of 30 μm×30 μm on the cross section of the negative electrode coating layer with a charge state of 50% along the thickness direction. The silicon content is 25% to 60%, preferably 40% to 55%, which can effectively increase the capacity of the negative electrode plate and improve the energy density of the lithium-ion battery.
[0012] In some embodiments of the present application, based on the sum of the masses of the graphite and the silicon-carbon material, the mass content of the silicon-carbon material is 3% to 50%, preferably 7% to 30%, and more preferably 10% to 15%, which can further improve the capacity of the negative electrode plate.
[0013] In some embodiments of the present application, the negative electrode plate is subjected to a buckle test with lithium metal as the counter electrode, and the voltage between 0 and 2 V vs Li + / Li range, the gram capacity C is between 500 and 1300 mAh / g; in some embodiments of the present application, the negative electrode plate is subjected to a buckle test with lithium metal as the counter electrode, the gram capacity within 0 to 0.8 V is E, the gram capacity within 0 to 0.3 V is D, and the range of D / E is between 45% and 75%.
[0014] In some embodiments of the present application, the X-ray diffraction spectrum of the negative electrode plate has one and only one diffraction peak in the range of 2θ of 20° to 30°, and the half-width of the diffraction peak is not greater than 2°. This is a characteristic diffraction peak of hard carbon material, which is due to the high degree of disorder of hard carbon, the disordered arrangement of internal microcrystals, and the disordered distribution of interlayer spacing.
[0015] In some embodiments of the present application, the negative electrode is subjected to Raman testing, and the Raman shift is 1338 cm -1 ±15cm -1 and 1595cm -1 ±15cm -1 The d peak and the g peak appear in the range, and the half-peak width of the d peak and the g peak is not less than 5 cm -1 The intensity ratio Id / Ig of the d peak and the g peak is not less than 0.3 and not more than 1.2.
[0016] A second aspect of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate described in the first aspect.
[0017] In some embodiments of the present application, the lithium-ion battery further comprises an electrolyte, a positive electrode plate and a separator; in some embodiments of the present application, the electrolyte comprises additives, the additives comprising 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile; in some embodiments of the present application, the mass percentage of 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile is 0.01% to 5% based on the weight of the electrolyte.
[0018] A third aspect of the present application provides an electronic device, which includes the lithium-ion battery described in the second aspect.
[0019] The present application uses a double-layer coating method and adjusts the composition and ratio of the two coating layers in the negative electrode plate to comprehensively improve the cycle performance, expansion performance and energy density of the lithium-ion battery containing the negative electrode plate, thereby increasing the life and stability of the lithium-ion battery. At the same time, the lithium-ion battery has better overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The SEM image and EDS mapping image are obtained by testing the cross section of the negative electrode coating layer along the thickness direction in Example 6 of the present application. DETAILED DESCRIPTION
[0021] The technical solution of the present application is further described below through specific examples and comparative examples, and the specific examples do not limit the protection scope of the present application. Some non-essential modifications and adjustments made by others based on the concept of the present application still fall within the protection scope of the present application.
[0022] For simplicity, for a certain parameter, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form a range that is not clearly recorded, and any lower limit can also be combined with other lower limits to form a range that is not clearly recorded, and any upper limit can be combined with any other upper limit to form a range that is not clearly recorded. In addition, each separately disclosed point or single numerical value itself can be combined with any other point or single numerical value as a lower limit or upper limit or with other lower limits or upper limits to form a range that is not clearly recorded. In the description herein, unless otherwise stated, "above", "below" includes this number.
[0023] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0024] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0025] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "include" and "comprise" and similar expressions are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0026] The first aspect of the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode coating layer disposed on the surface of the negative electrode current collector, wherein the negative electrode coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is located on the surface of the negative electrode current collector, and the second coating layer is located on the surface of the first coating layer; the first coating layer contains hard carbon, and the second coating layer contains graphite and silicon-carbon materials; the thickness of the first coating layer accounts for 20% to 85% of the thickness of the negative electrode coating layer, preferably 25% to 75%, and more preferably 45% to 65%. Specifically, the thickness of the first coating layer accounts for 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or a range consisting of any two of the above values. When the ratio of the thickness of the first coating layer to the thickness of the negative electrode coating layer is within the above range, high gram capacity and energy density as well as comprehensively improved lithium ion battery performance such as expansion performance, cycle performance and rate performance can be taken into account.
[0027] In the negative electrode plate provided in the present application, the first coating layer contains hard carbon, and the addition of hard carbon can effectively improve the expansion and cycle performance of the negative electrode plate; the second coating layer contains graphite and silicon-carbon material, and the addition of silicon-carbon material can effectively increase the capacity of the negative electrode plate, and when mixed with graphite, the expansion of silicon-carbon material can be alleviated.
[0028] In some embodiments of the present application, gaps exist inside the graphite particles, which can further improve the expansion of the negative electrode sheet.
[0029] In some embodiments of the present application, the graphite includes natural graphite and artificial graphite.
[0030] In some embodiments of the present application, within the range of 50 μm × 50 μm on the cross section of the negative electrode coating layer along the thickness direction, the ratio of the number of graphite particles to the number of silicon-carbon material particles is 0.20 to 2.00, preferably, the ratio of the number of graphite particles to the number of silicon-carbon material particles is 0.50 to 1.80. Specifically, the ratio of the number of particles can be 0.20, 0.40, 0.60, 0.80, 1.00, 1.20, 1.40, 1.60, 1.80, 2.00 or a range consisting of any two of the above values. When the ratio of the number of graphite particles to the number of silicon-carbon material particles is within the above range, the energy density of the lithium-ion battery can be effectively improved while taking into account the cyclic expansion performance of the lithium-ion battery.
[0031] In some embodiments of the present application, a spot scan test is performed on the silicon content in the second coating layer within a range of 30 μm×30 μm on a cross section of the negative electrode coating layer with a charge state of 50% along the thickness direction, and the silicon content is 25% to 60%, preferably 40% to 55%. Specifically, the silicon content can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two of the above values, which can effectively increase the capacity of the negative electrode sheet and improve the energy density of the lithium-ion battery.
[0032] In some embodiments of the present application, based on the sum of the masses of the graphite and the silicon-carbon material, the mass content of the silicon-carbon material is 3% to 50%, preferably 7% to 20%, and more preferably 10% to 15%. Specifically, the mass content of the silicon-carbon material can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of the above values, which can further increase the capacity of the negative electrode sheet.
[0033] In some embodiments of the present application, the negative electrode plate is subjected to a buckle test with lithium metal as the counter electrode, and the voltage at 0-2V vs Li + / Li range, the gram capacity C is between 500 and 1300 mAh / g; in some embodiments of the present application, the negative electrode plate is subjected to a buckle test with lithium metal as the counter electrode, the gram capacity within 0 to 0.8 V is E, the gram capacity within 0 to 0.3 V is D, and the range of D / E is between 45% and 75%.
[0034] In some embodiments of the present application, the X-ray diffraction spectrum of the negative electrode plate has one and only one diffraction peak in the range of 2θ of 20° to 30°, and the half-width of the diffraction peak is not greater than 2°. This is a characteristic diffraction peak of hard carbon material, which is due to the high degree of disorder of hard carbon, the disordered arrangement of internal microcrystals, and the disordered distribution of interlayer spacing.
[0035] In some embodiments of the present application, the negative electrode is subjected to Raman testing, and the Raman shift is 1338 cm -1 ±15cm -1 and 1595cm -1 ±15cm -1 The d peak and the g peak appear in the range, and the half-peak width of the d peak and the g peak is not less than 5 cm -1, the value of the intensity ratio Id / Ig of the d peak to the g peak is not less than 0.3 and not more than 1.2. Specifically, the value of Id / Ig can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or a range consisting of any two of the above values.
[0036] The negative electrode plate provided in the present application also includes a negative electrode current collector, a binder, a conductive agent and other optional additives.
[0037] In some embodiments of the present application, the negative electrode current collector may be copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0038] In some embodiments of the present application, the negative electrode coating layer may be disposed on one surface of the negative electrode current collector. In some embodiments of the present application, the negative electrode coating layer may be disposed on both surfaces of the negative electrode current collector.
[0039] In some embodiments of the present application, the binder can be polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0040] In some embodiments of the present application, the conductive agent may be a carbon-based material, a metal-based material, a conductive polymer and a mixture thereof; in some embodiments of the present application, the carbon-based material is selected from carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof; in some embodiments of the present application, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver; in some embodiments of the present application, the conductive polymer is a polyphenylene derivative.
[0041] A second aspect of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate described in the first aspect.
[0042] In some embodiments of the present application, the lithium-ion battery further includes a positive electrode plate, an electrolyte and a separator.
[0043] In some embodiments of the present application, the electrolyte includes additives, and the additives include 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile; in some embodiments of the present application, the mass percentage of 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile is 0.01% to 5% based on the weight of the electrolyte.
[0044] In some embodiments of the present application, the positive electrode sheet includes a current collector and a positive electrode coating layer located on the surface of the current collector, and the positive electrode coating layer includes a positive electrode active material, a binder, and a conductive carbon additive. The present application has no particular restrictions on the positive electrode current collector, the positive electrode active material, the conductive agent, and the binder, as long as the purpose of the present application can be achieved.
[0045] In some embodiments of the present application, the positive electrode active material includes but is not limited to lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), ternary positive electrode active material (NCM333, NCM523, NCM622, NCM811, NCA, etc.), lithium manganese oxide (LiMn2O4), lithium-rich manganese-based positive electrode (xLi2MnO3·(1-x)LiMO2), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) and the like; in some embodiments of the present application, the positive electrode current collector may include aluminum; in some embodiments of the present application, the binder may include but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.; in some embodiments of the present application, the conductive material may include but is not limited to: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof; in some embodiments of the present application, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof; in some embodiments of the present application, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments of the present application, the conductive polymer is a polyphenylene derivative.
[0046] The present application has no particular restrictions on the isolation membrane, as long as it can achieve the purpose of the present application. In some embodiments of the present application, the isolation membrane may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0047] A third aspect of the present application provides an electronic device, which includes the lithium-ion battery described in the second aspect.
[0048] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, drones, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0049] The present application is described in more detail below through examples.
[0050] Example 1
[0051] Preparation of negative electrode
[0052] 1) Preparation of graphite: Natural graphite was used, with a gram capacity of 360 mAh / g and a particle size Dv50 of 14 μm.
[0053] 2) Preparation of silicon-carbon material: Bisphenol A (PBA) and hexamethylenetetramine (HMT) were mixed in a molar ratio of 6:4 to form a mixture, and the mixing method was ball milling, and the ball milling speed was 600r / min, and the ball milling time was 5h. The ball-milled mixture was heated to 180°C and kept warm for 12h for curing. The cured mixture was transferred to a box furnace, and heated to 900°C for carbonization for 2h under a nitrogen atmosphere, and then cooled and transferred to a rotary kiln for activation for 12h under a carbon dioxide atmosphere to obtain a porous carbon skeleton, and the activation temperature was 900°C. After crushing and grading (Dv50 is 8μm), the porous carbon skeleton continues to be heated to 300°C at a rate of 2°C / min in a tubular furnace under an argon atmosphere, and then the atmosphere is switched to a silane mixture (30% silane and 70% argon by mass) and continued to be heated to 500°C. After deposition at 500°C for 15 hours, the atmosphere is switched to an acetylene mixture (50% acetylene and 50% argon by mass) and continued to be deposited at 500°C for 8 hours, then switched to nitrogen, and then cooled to room temperature 25°C to obtain a silicon-carbon material.
[0054] 3) Preparation of hard carbon: Commercial coconut shell is used as raw material. The specific preparation process is as follows: weigh 100g of coconut shell, crush it into particles less than 1mm, soak it in 1M sodium hydroxide solution for 10h, filter and dry it; then, in a nitrogen atmosphere, heat the dried alkali-treated coconut shell to 800℃ at a heating rate of 5℃ / min in a tubular furnace, keep it warm for 2h and then cool it naturally; wash the obtained black powder with water twice, then acid wash it twice, and then wash it with water twice, dry it and grade it by air flow crushing (Dv50 is 5μm), then heat the sample to 1100℃ at a heating rate of 5℃ / min, keep it warm for 2h, and then cool it to 880℃, switch the atmosphere to CH4, keep it warm for 5h, switch the atmosphere to N2 again, and then start to cool the room temperature naturally to 25℃ to obtain hard carbon.
[0055] 4) Preparation of negative electrode sheets: The negative electrode active material hard carbon, the negative electrode active material graphite and the silicon-carbon material are mixed in the proportions in Table 1 (the mass content of the silicon-carbon material is calculated based on the sum of the masses of the graphite and the silicon-carbon material) with the binder styrene-butadiene rubber (SBR) and the thickener sodium carboxymethyl cellulose (CMC) in a mass ratio of 97:2:1 in an appropriate amount of solvent deionized water, and then the negative electrode slurries are respectively coated on the negative electrode collector copper foil, wherein the slurry containing the negative electrode active material hard carbon is coated on one surface of the negative electrode collector to form a first coating layer, and the slurry containing the negative electrode active material graphite and the silicon-carbon material is coated on the surface of the first coating layer to form a second coating layer, and the coating thicknesses of the first coating layer and the second coating layer are both in accordance with the ratios provided in Table 1; then after drying at 85°C, cold pressing, cutting, slitting, and vacuum drying at 120°C for 12 hours, the negative electrode sheet is obtained.
[0056] Preparation of positive electrode
[0057] The positive electrode active material (lithium cobalt oxide in all embodiments of the present application), the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in a proper amount of N-methylpyrrolidone (NMP) solvent at a weight ratio of 97:1.4:1.6 to form a uniform positive electrode slurry, wherein the solid content of the positive electrode slurry was 72wt%. The slurry was coated on one surface of the positive electrode current collector aluminum foil, dried at 85°C, and then cold pressed, cut into pieces, and cut, and dried at 85°C under vacuum conditions for 4 hours to obtain a positive electrode sheet.
[0058] Preparation of electrolyte
[0059] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed in a mass ratio of EC:PC:DEC=50:20:30, and then fluoroethylene carbonate is added. After dissolution and sufficient stirring, lithium salt LiPF6 is added and mixed evenly to obtain an electrolyte, wherein, based on the mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, and the mass percentage of fluoroethylene carbonate is 2.5%.
[0060] Preparation of isolation membrane
[0061] A 7 μm thick polyethylene (PE) porous polymer film was used as the isolation membrane.
[0062] Preparation of lithium-ion batteries
[0063] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play an isolating role. Then they are wound, the pole ears are welded, and placed in the outer packaging foil aluminum-plastic film. The electrolyte is injected, and after vacuum packaging, standing, formation, shaping, capacity testing and other processes, a soft-pack lithium-ion battery is obtained.
[0064] Examples 2 to 13, Comparative Example 1
[0065] The differences between the preparation processes of Examples 2 to 13 and the preparation process of Comparative Example 1 and the preparation process of Example 1 lie in the thickness ratio of the first coating layer, the mass content of the silicon-carbon material, the ratio of the number of graphite particles to the number of silicon-carbon material particles, and the content of silicon in the silicon-carbon material when preparing the negative electrode sheet, as shown in Table 1.
[0066] Examples 14 to 16, Comparative Example 2
[0067] The difference between the processes of Examples 14 to 16 and Comparative Example 2 and Example 1 is only that the types and contents of electrolyte additives are different during the electrolyte preparation process. Among them, in Examples 14 to 15, the mass percentage of the two additives is 1:1, as shown in Table 3.
[0068] Test Method
[0069] The negative electrode active materials, negative electrode plates and lithium-ion batteries in the above-mentioned embodiments and comparative examples were subjected to the following tests, respectively. The test results are shown in Tables 2 and 3.
[0070] (1) Scanning electron microscopy characterization: The lithium-ion battery was discharged to 3.0 V at 1.0 C and then charged to 50% of the rated capacity. The battery was disassembled in a glove box to obtain the negative electrode sheet, which was then transferred to a drying room with a humidity of less than 2%. The cross-section of the negative electrode coating layer along the thickness direction was obtained by ion polishing and quickly transferred to a scanning electron microscope for characterization. First, a 50μm×50μm range of the cross section was selected for dark-field SEM characterization, and the internal morphology of the particles was carefully recorded. The particles with at least one gap of not less than 10nm×100nm inside the particles were marked as graphite particles; then, the backscatter photography mode was turned on, and in the same SEM area, the particles with higher brightness than graphite particles under backscatter conditions and no gaps inside the particles were marked as silicon-carbon material particles; finally, the particles other than graphite particles and silicon-carbon material particles were marked as hard carbon particles; then, an EDS surface scan was performed in the above-mentioned area to obtain a mapping of carbon and silicon elements, and the coating layer containing silicon elements was marked as the second coating layer, containing graphite and silicon-carbon materials; and the remaining layer area was the first coating layer, containing hard carbon; the first and second coating layers were measured respectively. The thickness of the first and second coating layers is measured at any ten positions on the cross section along the thickness direction, and the average values are calculated, that is, the thickness of the first coating layer and the second coating layer. The thickness of the negative electrode coating layer is the sum of the thickness of the first coating layer and the thickness of the second coating layer); then, in the second coating layer in the cross section, a range of 30 μm × 30 μm is selected to repeat the above operation, and the number of graphite particles and silicon-carbon material particles is recorded respectively. After selecting 5 30 μm × 30 μm areas for the above operation, the average number of graphite particles and silicon-carbon material particles is calculated respectively; then, the silicon-carbon material particles are subjected to EDS elemental analysis to obtain element distribution mapping and spectra of elements such as C and Si, and the mass content of each element is obtained, and the content of silicon is recorded.
[0071] (2) Raman test: The negative electrode sheets of each embodiment and comparative example were tested using a spectrometer (JobinYvon LabRAM HR), with a light source of 532 nm and a test range of 50 cm -1 Up to 2000cm -1 After the test is completed, pay attention to 1000~2000cm -1 For characteristic peaks within the range, the maximum point of the peak is taken as the peak position of the peak, and 1 / 2 of the difference of the horizontal coordinates at half the peak is taken as the half-peak width of the peak. -1 ±15cm -1 and 1595cm -1 ±15cm -1 The peaks within the range are marked as d peak and g peak, respectively, and their intensities are identified after deducting the baseline to obtain the value of their intensity ratio Id / Ig.
[0072] (3) XRD test: The negative electrode was placed on a sample carrier for powder XRD test. The test range was 10° to 90° and the scanning speed was 5° / min. After the test, the characteristic peaks in the range of 15° to 35° were focused on. The maximum point of the peak was taken as the peak position of the peak, and 1 / 2 of the difference in the horizontal coordinates at half the peak was taken as the half-peak width of the peak.
[0073] (4) Button test: Punch the negative electrode sheet into a disc with a diameter of 14 mm, weigh it (weigh the corresponding empty copper foil area to obtain the weight of the substrate) and calculate the weight of the negative electrode active material before assembling the button battery. The button battery is assembled with the obtained negative electrode sheet as the working electrode and the lithium sheet as the counter electrode. The two are aligned up and down and separated by an isolation membrane and the electrolyte is added to form a button battery. After the button battery is assembled, it is left to stand for 8 hours before the test begins. First, it is discharged at a constant current density of 25 mA / g to 0 V vs Li+ / Li, and then discharged at a constant voltage of 0 V to a current density of 2.5 mA / g. The gram capacity of this step is recorded; then it is charged at a constant current density of 25 mA / g to 2.0 V vs Li+ / Li. For the obtained charging capacity, the gram capacity of 0-0.3 V is taken as D, the gram capacity of 0-0.8 V is taken as E, and the gram capacity of 0-2.0 V is taken as C.
[0074] (5) Capacity retention rate test: The lithium-ion batteries in each embodiment and comparative example were left at rest for 5 minutes at a test temperature of 25°C, then charged at a constant current of 1C to a voltage of 4.5V, and then charged at a constant voltage of 0.05C; discharged at a constant current of 1C to a voltage of 3V, which was recorded as one cycle, and the capacity at this time was recorded as D0. This cycle was repeated for 600 times, and the last discharge capacity was recorded as D1; after 600 cycles at 25°C, the capacity retention rate of the lithium-ion battery was D1 / D0×100%. Five samples were tested for each embodiment or comparative example, and the average value was taken.
[0075] (8) Expansion rate test: In the above-mentioned cycle process, after the first cycle, the lithium-ion battery is discharged to 50% SOC, and the thickness at the diagonal center is tested and recorded as h0. After every 100 cycles, the thickness of the lithium-ion battery is recorded at the same position at 50% SOC using the same test method. After 800 cycles, the thickness of the lithium-ion battery is obtained to be h8. At this time, the expansion rate of the lithium-ion battery is (h8-h0) / h0×100%.
[0076] (9) Volumetric energy density: Then, at room temperature, charge the battery to 4.5 V at a current of 1 C, then charge it to 0.05 C at a constant voltage of 4.5 V; let it stand for 5 min, then discharge it to 3.0 V at a constant current of 0.025 C, let it stand for 5 min, record the capacity at this time as D, in mAh, then charge the lithium-ion battery to 4.0 V at 1.0 C, measure the length, width and thickness of the lithium-ion battery at this time, and calculate the volume V of the lithium-ion battery, in mm 3 , volume energy density calculation: VED = (D × 3.9 × 1000) / V, unit is Wh / L. Five samples were tested for each embodiment or comparative example, and the average value was taken.
[0077] Table 1 Preparation parameters of negative electrode sheet
[0078]
[0079] Table 2 Performance parameters of negative electrode sheet and lithium-ion battery
[0080]
[0081]
[0082] Table 3 Types and mass percentages of electrolyte additives added to lithium-ion batteries and performance test results
[0083]
[0084] It can be seen from Table 1 that by setting the negative electrode coating layer to include a first coating layer and a second coating layer, the first coating layer contains hard carbon, the second coating layer contains graphite and silicon-carbon material, and the thickness of the first coating layer accounts for 20% to 85% of the thickness of the negative electrode coating layer, the cycle performance, expansion performance, gram capacity and energy density of the lithium-ion battery are comprehensively improved.
[0085] It can be seen from Examples 1 to 4 that the cycle capacity retention rate and expansion rate of the lithium-ion battery are significantly improved with the change in the thickness of the first coating layer. It can be seen from Examples 5 to 13 that by adjusting the thickness ratio of the first coating layer and the mass content of the silicon-carbon material, a lithium-ion battery with improved gram capacity, energy density and cycle expansion performance can be obtained. Figure 1 The SEM image and EDS mapping image tested in the cross section of the negative electrode coating layer with a charge state of 50% in Example 6 in the 30μm×30μm range along the thickness direction can be analyzed by combining the two to show that the negative electrode coating layer contains a first coating layer and a second coating layer, and the first coating layer contains hard carbon (first active material) particles, and the second coating layer contains graphite (second active material) particles and silicon-carbon material (third active material) particles.
[0086] It can be seen from Example 1, Examples 14-16 and Comparative Example 2 that when the silicon element and hard carbon have the same content, the cycle capacity retention and expansion performance of the lithium ion battery are further improved by adding the electrolyte additives 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile, indicating that 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile form a better flexible low-impedance interface between the first active layer and the second active layer, thereby improving the cycle expansion performance of the lithium ion battery.
[0087] The above is a detailed introduction to the negative electrode plate and its preparation method and application of the present application. Specific examples are used in this article to illustrate the scheme of the present application, but the specific examples are only used to help understand the main purpose and core of the present application and do not constitute a limitation on the scope of protection; technical personnel in this field can improve the scheme of the present application based on the ideas of the present application without exceeding the scope of the present application.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode coating layer disposed on the surface of the negative electrode current collector, wherein the negative electrode coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is disposed on the surface of the negative electrode current collector, and the second coating layer is disposed on the surface of the first coating layer; the first coating layer contains hard carbon, and the second coating layer contains graphite and silicon-carbon material; The thickness of the first coating layer accounts for 20% to 85% of the thickness of the negative electrode coating layer.
2. The negative electrode sheet according to claim 1, characterized in that: The thickness of the first coating layer accounts for 25% to 75% of the thickness of the negative electrode coating layer; Preferably, the thickness of the first coating layer accounts for 45% to 65% of the thickness of the negative electrode coating layer.
3. The negative electrode sheet according to claim 1, characterized in that: There are gaps inside the graphite particles.
4. The negative electrode sheet according to claim 1, characterized in that: In the range of 50 μm×50 μm on the cross section of the negative electrode coating layer along the thickness direction, the ratio of the number of graphite particles to the number of silicon-carbon material particles is 0.20-2.00, preferably, the ratio of the number of graphite particles to the number of silicon-carbon material particles is 0.50-1.
80.
5. The negative electrode sheet according to claim 1, characterized in that: The silicon content in the second coating layer is tested by spot scanning within a range of 30 μm×30 μm on a cross section of the negative electrode coating layer with a charge state of 50% along the thickness direction. The silicon content is 25% to 60%, preferably 40% to 55%.
6. The negative electrode sheet according to claim 1, characterized in that: Based on the sum of the mass of the graphite and the silicon-carbon material, the mass content of the silicon-carbon material is 3% to 50%, preferably 7% to 30%.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The negative electrode sheet satisfies at least one of the following conditions (i) to (iv): (i) The negative electrode plate is subjected to a buckle test with lithium metal as the counter electrode, at 0-2V vs Li + / Li range, the gram capacity C is between 500~1300mAh / g; (ii) performing a buckle test on the negative electrode sheet with lithium metal as the counter electrode, wherein the gram capacity within 0 to 0.8 V is E, the gram capacity within 0 to 0.3 V is D, and the range of D / E is between 45% and 75%; (iii) the X-ray diffraction spectrum of the negative electrode has one and only one diffraction peak in the range of 2θ of 20° to 30°, and the half-peak width of the diffraction peak is not greater than 2°; (iv) Raman test was performed on the negative electrode. The Raman shift was 1338 cm -1 ±15cm -1 and 1595cm -1 ±15cm -1 The d peak and the g peak appear in the range, and the half-peak width of the d peak and the g peak is not less than 5 cm -1 The intensity ratio Id / Ig of the d peak and the g peak is not less than 0.3 and not more than 1.
2.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode sheet as claimed in any one of claims 1 to 7.
9. The lithium ion battery according to claim 8, characterized in that: The lithium-ion battery further comprises an electrolyte, a positive electrode plate and a separator; the electrolyte comprises an additive, and the additive comprises 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile; Preferably, based on the mass of the electrolyte, the mass percentage of the 5-methyl-1,3-dioxolane-2,4-dione and succinonitrile is 0.01% to 5%.
10. An electronic device comprising the lithium ion battery according to claim 9.